Binder composition as well as preparation method and application thereof
By using a binder composition of glycidyl ester compound and branched fluorobenzene compound in the negative active layer of the sodium ion battery, the problem of poor bondability between the active layer and the current collector is solved, and the performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411774785.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
AI Technical Summary
In sodium ion batteries, the bonding between the active layer of the positive and negative electrode and the current collector is poor, resulting in a decrease in the first-time efficiency and a rapid cycle life decay, which affects the battery performance.
Using a binder composition, including a glycidyl ester compound and a fluorobenzene compound grafted on the glycidyl ester compound, the mixture is mixed with a glycidyl ester epoxy resin after the introduction of a nitro group on the fluorobenzene compound to form Adhesive compositions are used to improve the adhesion between the negative electrode active layer and the current collector.
The peeling force of the negative electrode is improved, the Hi-pot defect rate is reduced when preparing the electrode sheet, and the low-temperature electrical performance and safety of sodium ion batteries are enhanced.
Smart Images

Figure BDA0005174149010000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and relates to a binder composition, a preparation method and an application thereof. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries have similar working principles and significant preparation cost advantages, and are expected to be widely used in the field of energy storage. In sodium-ion batteries, the performance of the positive and negative electrodes plays a very important role in the performance of the battery. The electrode generally includes a current collector and an active layer. The bonding between the active layer and the current collector plays a very important role in the performance of the battery. Poor bonding between the active layer and the current collector will lead to an increase in the hi-pot bad ratio, which in turn leads to a decrease in the first efficiency and a rapid decay of the cycle life.
[0003] The active layer generally includes active materials and binders. In order to increase conductivity, a conductive agent can also be added. The binder binds the negative electrode active material with other components and the current collector. The performance of the binder will directly affect the performance of the electrode, and then affect the performance of the sodium ion battery.
[0004] Therefore, providing a high-performance binder to improve the performance of the electrode is of great significance for the development and application of sodium-ion batteries. Summary of the invention
[0005] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide an adhesive composition and a preparation method and application thereof.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a binder composition, comprising a glycidyl ester compound and a fluorobenzene compound grafted onto the glycidyl ester compound.
[0008] In a second aspect, the present invention provides a method for preparing the binder composition according to the first aspect, the preparation method comprising the following steps:
[0009] After a nitro group is introduced into the fluorobenzene compound, the fluorobenzene compound having the nitro group is mixed with a glycidyl ester epoxy resin and reacted to obtain an adhesive composition.
[0010] Preferably, the fluorobenzene compound includes at least one of fluorobenzene, difluoroaniline, trifluoroaniline and tetrafluorophenol.
[0011] Preferably, the glycidyl ester epoxy resin includes at least one of bisphenol diglycidyl ester, diphenol propane and polyphenol glycidyl ester.
[0012] Preferably, the mass ratio of the fluorobenzene compound having a nitro group to the glycidyl ester epoxy resin is (0.5-2):(3-6).
[0013] Preferably, the mixing of the fluorobenzene compound having a nitro group and the glycidyl ester epoxy resin is accompanied by stirring.
[0014] Preferably, the time for mixing the fluorobenzene compound having a nitro group with the glycidyl ester epoxy resin is 180 min to 240 min.
[0015] Preferably, the process of mixing the fluorobenzene compound having a nitro group with the glycidyl ester epoxy resin is carried out at room temperature.
[0016] As a preferred technical solution of the preparation method described in the present invention, the method of introducing a nitro group into the fluorobenzene compound is: mixing the fluorobenzene compound, a catalyst and concentrated nitric acid, allowing the fluorobenzene compound to react with the nitric acid to obtain a fluorobenzene compound having a nitro group.
[0017] Preferably, the reaction of the fluorobenzene compound with nitric acid is accompanied by stirring.
[0018] Preferably, the reaction time of the fluorobenzene compound and nitric acid is 30 min to 60 min.
[0019] Preferably, the temperature for the reaction of the fluorobenzene compound with nitric acid is 40°C to 70°C.
[0020] Preferably, the pressure of the reaction of the fluorobenzene compound with nitric acid is controlled within the range of 1 MPa to 3 MPa.
[0021] Preferably, the catalyst comprises concentrated sulfuric acid.
[0022] Preferably, the mass ratio of the fluorobenzene compound, the catalyst and concentrated nitric acid is (0.5-2):(0.5-2):(0.5-2).
[0023] Preferably, the reaction of the fluorobenzene compound with nitric acid is carried out in a closed environment, and a protective gas is passed through the closed environment.
[0024] Preferably, the protective gas includes at least one of helium, nitrogen and argon.
[0025] In a third aspect, the present invention provides a negative electrode, comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material and a first binder, the first binder comprising the binder composition as described in the first aspect or the binder composition obtained by the preparation method as described in the second aspect.
[0026] Preferably, the negative electrode active material is hard carbon.
[0027] Preferably, the peeling force of the negative electrode active material layer is greater than 0.9N.
[0028] Preferably, the negative electrode further comprises a conductive carbon material, and the conductive carbon material comprises at least one of conductive carbon black Super P, carbon nanotubes and graphite.
[0029] Preferably, the negative electrode further comprises a curing agent, and the curing agent comprises at least one of diaminodicyclohexylmethane, triethylene glycolamine, boron trifluoride glycerol and boron trifluoride aniline.
[0030] Preferably, the mass ratio of the negative electrode active material, the conductive carbon material, the first binder and the curing agent is (84-90):(5-7):(20-40):(0.5-1).
[0031] In a fourth aspect, the present invention provides a method for preparing the negative electrode as described in the third aspect, the preparation method comprising the following steps:
[0032] (1) mixing a negative electrode active material with a first binder and first stirring to obtain a negative electrode slurry, wherein the first binder includes the binder composition described in the first aspect or the binder composition obtained by the preparation method described in the second aspect;
[0033] (2) coating the negative electrode slurry on a negative electrode current collector and drying to obtain a negative electrode;
[0034] Preferably, the negative electrode active material is hard carbon.
[0035] Preferably, after the negative electrode active material and the first binder are mixed and stirred for the first time, a curing agent is added and stirred for the second time to obtain a negative electrode slurry.
[0036] Preferably, the first stirring time is 120 min to 220 min.
[0037] Preferably, the second stirring time is 20 min to 45 min.
[0038] Preferably, the drying temperature is 90°C to 95°C.
[0039] In a fifth aspect, the present invention provides a battery, comprising the negative electrode described in the third aspect or the negative electrode obtained by the preparation method described in the fourth aspect.
[0040] Preferably, the capacity retention rate of the battery at -30°C is greater than 90%.
[0041] Preferably, the number of cycles at which the capacity of the battery decays to 80% of the initial capacity at room temperature is greater than 2000 cycles.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The binder composition provided by the present invention has the effects of modification and curing. On the one hand, the epoxy group in the glycidyl ester epoxy resin has excellent bonding properties to metal materials such as aluminum, iron, and copper. Applying it to the electrode can greatly improve the bonding between the current collector and the active layer, thereby improving the peeling force of the negative electrode and reducing the Hi-pot defect rate when preparing the pole piece; on the other hand, the glycidyl ester epoxy resin has good ultra-low temperature resistance and can improve the low-temperature electrical properties of the sodium ion battery. At the same time, the fluorobenzene compound in the binder composition has flame retardancy and can improve the safety of the battery cell.
[0044] (2) The present invention can improve the adhesion between the current collector and the active layer by introducing the above-mentioned binder composition in the preparation of the negative electrode, thereby improving the peeling force of the negative electrode and reducing the Hi-pot defect rate when preparing the electrode sheet; moreover, it can improve the low-temperature electrical performance and safety of the sodium ion battery.
[0045] (3) The preparation process of the negative electrode provided by the present invention is simple and can be prepared using an existing production line, making it easy to realize industrial production. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0047] In the present invention, "first" and "second" are merely distinctions in name and have no substantial meaning.
[0048] In one embodiment, the present invention provides a binder composition, which includes a glycidyl ester compound and a fluorobenzene compound grafted onto the glycidyl ester compound.
[0049] In the present invention, the adhesive composition is a compound formed by chemical reaction between a glycidyl ester epoxy resin and a fluorobenzene compound, wherein the molecules of the glycidyl ester epoxy resin are uniformly distributed on the molecular chain of the fluorobenzene compound.
[0050] The binder composition provided in one embodiment of the present invention has the effects of modification and curing. On the one hand, the epoxy group in the glycidyl ester epoxy resin has excellent bonding properties to metal materials such as aluminum, iron, and copper. Applying it to the electrode can greatly improve the bonding between the current collector and the active layer, thereby improving the peeling force of the negative electrode and reducing the Hi-pot defect rate when preparing the pole piece; on the other hand, the glycidyl ester epoxy resin has good ultra-low temperature resistance, which can make the sodium ion battery under low temperature conditions, further improve the low-temperature electrical performance of the sodium ion battery. At the same time, the fluorobenzene compound in the binder composition has flame retardancy and can improve the safety of the battery cell.
[0051] In another embodiment, the present invention provides a method for preparing the above-mentioned binder composition, the preparation method comprising the following steps:
[0052] After the nitro group is introduced into the fluorobenzene compound, the fluorobenzene compound having the nitro group is mixed with a glycidyl ester epoxy resin and reacted to introduce the epoxy group of the glycidyl ester epoxy resin into the nitro group to obtain a binder composition.
[0053] In one embodiment, the fluorobenzene compound includes at least one of fluorobenzene, difluoroaniline, trifluoroaniline and tetrafluorophenol.
[0054] Fluorobenzene has a certain lubricity, which can optimize the lubricity of the binder composition and prevent the surface of the active layer from being too rough, thereby having better processing performance. For example, if the surface of the active layer is too rough, it will easily lead to wrinkling of the pole piece due to the roughness of the pole piece during the process of winding the battery cell.
[0055] In one embodiment, the glycidyl ester epoxy resin includes at least one of bisphenol diglycidyl ester, diphenol propane and polyphenol glycidyl ester;
[0056] In one embodiment, the mass ratio of the fluorobenzene compound having a nitro group to the glycidyl ester epoxy resin is (0.5-2):(3-6), wherein the selection range of the fluorobenzene compound having a nitro group is "0.5-2", for example, it can be 0.5, 0.6, 0.7, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.7, 1.8, 1.9 or 2, etc.
[0057] In one embodiment, the mixing of the fluorobenzene compound having a nitro group and the glycidyl ester epoxy resin is accompanied by stirring;
[0058] In one embodiment, the mixing time of the fluorobenzene compound having a nitro group and the glycidyl ester epoxy resin is 180 min to 240 min, for example, 180 min, 185 min, 190 min, 195 min, 200 min, 205 min, 215 min, 225 min, 235 min or 240 min.
[0059] In one embodiment, the process of mixing the fluorobenzene compound having a nitro group with the glycidyl ester epoxy resin is performed at room temperature.
[0060] In one embodiment, the method of introducing a nitro group into the fluorobenzene compound is: mixing the fluorobenzene compound, a catalyst and concentrated nitric acid, and reacting the fluorobenzene compound with the nitric acid to obtain the fluorobenzene compound having a nitro group.
[0061] In one embodiment, the reaction is accompanied by stirring.
[0062] In one embodiment, the reaction time is 30 min to 60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.
[0063] In one embodiment, the reaction temperature is 40°C to 70°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C.
[0064] In one embodiment, the reaction pressure is controlled in the range of 1 MPa to 3 MPa. For example, the pressure may be 1 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.5 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa, 2 MPa, 2.1 MPa, 2.2 MPa, 2.3 MPa, 2.4 MPa, 2.5 MPa, 2.6 MPa, 2.7 MPa or 2.9 MPa.
[0065] In one embodiment, the catalyst comprises concentrated sulfuric acid.
[0066] In one embodiment, the mass ratio of the fluorobenzene compound, the catalyst and the concentrated nitric acid is (0.5-2):(0.5-2):(0.5-2), wherein the selection range of the fluorobenzene compound is "0.5-2", for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.3, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, etc.; the selection range of the catalyst is "0.5-2", for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.3, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, etc.; the selection range of concentrated nitric acid is "0.5-2", for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.3, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, etc.
[0067] In one embodiment, the reaction is carried out in a closed environment, and a protective gas is passed through the closed environment.
[0068] In one embodiment, the protective gas includes at least one of helium, nitrogen and argon.
[0069] In another embodiment, the present invention provides a negative electrode, which includes a negative electrode collector and a negative electrode active material layer located on at least one side of the surface of the negative electrode collector, the negative electrode active material layer includes a negative electrode active material and a first binder, and the first binder includes the binder composition as described above or the binder composition obtained by the preparation method as described above.
[0070] In one embodiment of the present invention, by introducing the above-mentioned binder composition in the preparation of the negative electrode, the adhesion between the current collector and the active layer can be improved, thereby improving the peeling force of the negative electrode and reducing the Hi-pot defect rate when preparing the electrode sheet; moreover, the low-temperature electrical performance and safety of the sodium ion battery can be improved.
[0071] In one embodiment, the negative electrode active material is hard carbon.
[0072] In one embodiment, the peeling force of the negative electrode active material layer is greater than 0.9 N. The greater the peeling force, the better the binding force of the negative electrode active material layer.
[0073] In one embodiment, the negative electrode further comprises a conductive carbon material, and the conductive carbon material comprises at least one of conductive carbon black Super P, carbon nanotubes and graphite.
[0074] In one embodiment, the negative electrode further includes a curing agent, and the curing agent includes at least one of diaminodicyclohexylmethane, triethylene glycol amine, boron trifluoride glycerol, and boron trifluoride aniline.
[0075] In one embodiment, the mass ratio of the negative electrode active material, the conductive carbon material, the first binder and the curing agent is (84-90): (5-7): (20-40): (0.5-1), wherein the selection range of the negative electrode active material is "84-90", for example, it can be 84, 84.5, 85, 86, 86.5, 87, 88, 88.5, 89, 89.5 or 90; the selection range of the conductive carbon material is "5-7", for example, it can be 5, 5.5, 6, 6.5 or 7, etc.; the selection range of the first adhesive is "20-40", for example, it can be 20, 21, 22, 23, 24, 25, 26, 26.5, 27, 27.5, 28, 29, 30, 31, 32, 32.5, 33, 34, 35, 35.5, 36, 37, 38, 38.5, 39 or 40, etc.; the selection range of the curing agent is "0.5-1", for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.
[0076] In another embodiment, the present invention provides a method for preparing the negative electrode as described above, the preparation method comprising the following steps:
[0077] (1) mixing a negative electrode active material with a first binder and first stirring to obtain a negative electrode slurry, wherein the first binder includes the binder composition as described above or the binder composition obtained by the preparation method as described above;
[0078] (2) coating the negative electrode slurry on a negative electrode current collector and drying to obtain a negative electrode;
[0079] In one embodiment, the negative electrode active material is hard carbon.
[0080] Hard carbon is a type of carbon that will not graphitize after high-temperature treatment above 2800°C. Its internal crystal arrangement is not required and the interlayer spacing is large. Compared with other negative electrode active materials, hard carbon can store more charge in the same volume, thereby improving the energy density and endurance of sodium-ion batteries.
[0081] The preparation process of the negative electrode provided by one embodiment of the present invention is simple, and can be prepared using an existing production line, making it easy to realize industrial production.
[0082] In one embodiment, the negative electrode further includes a conductive carbon material. In step (1), the conductive carbon material is mixed with the negative electrode active material and the first binder and stirred for the first time.
[0083] In one embodiment, after the negative electrode active material and the first binder are mixed and stirred for the first time, a curing agent is added and stirred for the second time to obtain a negative electrode slurry.
[0084] In one embodiment, the first stirring time is 120 min to 220 min, for example, it can be 120 min, 125 min, 130 min, 135 min, 140 min, 145 min, 150 min, 160 min, 165 min, 170 min, 175 min, 180 min, 185 min, 190 min, 195 min, 200 min, 205 min, 210 min, 215 min or 220 min, etc.
[0085] In one embodiment, the second stirring time is 20 min to 45 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min or 45 min.
[0086] In one embodiment, the drying temperature is 90°C to 95°C, for example, 90°C, 91°C, 92°C, 93°C, 94°C or 95°C.
[0087] In another embodiment, the present invention provides a battery, which includes the negative electrode described above or the negative electrode obtained by the above preparation method.
[0088] In one embodiment, the battery includes a positive electrode, a negative electrode and a separator, wherein the separator is disposed between the positive electrode and the negative electrode to isolate the positive electrode from the negative electrode to avoid short circuit.
[0089] In one embodiment, the capacity retention rate of the battery at -30°C is greater than 90%. In the battery of the present invention, since the first binder is introduced into the negative electrode, the glycidyl ester epoxy resin therein has good ultra-low temperature resistance, thus effectively improving the low temperature performance of the battery.
[0090] In one embodiment, the number of cycles at which the capacity of the battery decays to 80% of the initial capacity at room temperature is greater than 2000 cycles. In the battery of the present invention, since the first binder is introduced into the negative electrode, the epoxy group in the glycidyl ester epoxy resin has excellent bonding properties to metal materials such as aluminum, iron, and copper. Applying it to the negative electrode can greatly improve the bonding between the current collector and the negative electrode active layer, thereby improving the cycle performance of the battery at room temperature.
[0091] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0092] The following are typical but non-limiting examples:
[0093] The "parts" in the embodiments of the present invention refer to parts by mass. The mass fraction of concentrated sulfuric acid is 70%, and the mass fraction of concentrated nitric acid is 86%.
[0094] Example 1
[0095] Provided is a binder composition, the preparation method of which comprises the following steps:
[0096] Weigh 3 parts of fluorobenzene, 3 parts of concentrated sulfuric acid, and 3 parts of concentrated nitric acid, add them into a container and stir evenly for 30 minutes. Control the temperature to 70°C and the pressure to 1 MPa. Pass argon gas in a closed environment to react fluorobenzene with nitric acid to generate a fluorobenzene compound with a nitro group.
[0097] After the fluorobenzene compound having a nitro group has reacted completely, the temperature is lowered to room temperature, 10 parts of bisphenol diglycidyl ester is weighed and added to the above solution, and stirred for 180 minutes to allow the epoxy group on the bisphenol diglycidyl ester to react with the nitro group of the fluorobenzene compound having a nitro group, so that the fluorobenzene compound is grafted onto the molecular chain of the bisphenol diglycidyl ester to obtain a binder composition.
[0098] Application Example 1
[0099] Provided is a negative electrode sheet, comprising a negative electrode current collector and a negative electrode layer arranged on the surface of the negative electrode current collector, wherein the negative electrode layer comprises a negative electrode active material (hard carbon), a conductive carbon material (Super P), a binder composition (Example 1) and a curing agent (diaminodicyclohexylmethane) in a mass ratio of 85:6:30:1.
[0100] A method for preparing the above-mentioned negative electrode sheet is provided, comprising the following steps:
[0101] The negative electrode active material, the binder composition and the conductive carbon material are mixed in NMP and stirred for the first time for 180 minutes, and then a curing agent is added and stirred for the second time for 30 minutes to obtain a negative electrode slurry. The negative electrode slurry is coated on a negative electrode collector and dried at 90° C. to obtain a negative electrode sheet.
[0102] Example 2
[0103] Provided is a binder composition, the preparation method of which comprises the following steps:
[0104] Weigh 6 parts of fluorobenzene, 3 parts of concentrated sulfuric acid, and 3 parts of concentrated nitric acid, add them into a container and stir evenly for 45 minutes. Control the temperature to 55°C and the pressure to 2MPa. Pass argon gas in a closed environment to react fluorobenzene with nitric acid to generate a fluorobenzene compound with a nitro group.
[0105] After the fluorobenzene compound having a nitro group has reacted completely, the temperature is lowered to room temperature, 17 parts of bisphenol diglycidyl ester is weighed and added to the above solution, and stirred for 210 minutes to allow the epoxy group on the bisphenol diglycidyl ester to react with the nitro group of the fluorobenzene compound having a nitro group, so that the fluorobenzene compound is grafted onto the molecular chain of the bisphenol diglycidyl ester to obtain a binder composition.
[0106] Application Example 2
[0107] Provided is a negative electrode sheet, comprising a negative electrode current collector and a negative electrode layer disposed on the surface of the negative electrode current collector, wherein the negative electrode layer comprises a negative electrode active material (hard carbon), a conductive carbon material (Super P), a binder composition (Example 2) and a curing agent (triethylene glycol amine) in a mass ratio of 88:7:20:0.5.
[0108] A method for preparing the above-mentioned negative electrode sheet is provided, comprising the following steps:
[0109] The negative electrode active material, the binder composition and the conductive carbon material are mixed in NMP and stirred for the first time for 200 minutes, and then a curing agent is added and stirred for the second time for 45 minutes to obtain a negative electrode slurry. The negative electrode slurry is coated on a negative electrode collector and dried at 95° C. to obtain a negative electrode sheet.
[0110] Example 3
[0111] Provided is a binder composition, the preparation method of which comprises the following steps:
[0112] Weigh 8 parts of fluorobenzene, 3 parts of concentrated sulfuric acid, and 3 parts of concentrated nitric acid, add them into a container and stir evenly for 60 minutes. Control the temperature to 40°C and the pressure to 3 MPa. Pass argon gas in a closed environment to react fluorobenzene with nitric acid to generate a fluorobenzene compound with a nitro group.
[0113] After the fluorobenzene compound having a nitro group has reacted completely, the temperature is lowered to room temperature, 24 parts of bisphenol diglycidyl ester is weighed and added to the above solution, and stirred for 240 minutes to allow the epoxy group on the bisphenol diglycidyl ester to react with the nitro group of the fluorobenzene compound having a nitro group, so that the fluorobenzene compound is grafted onto the molecular chain of the bisphenol diglycidyl ester to obtain a binder composition.
[0114] Application Example 3
[0115] Provided is a negative electrode sheet, comprising a negative electrode current collector and a negative electrode layer disposed on the surface of the negative electrode current collector, wherein the negative electrode layer comprises a negative electrode active material (hard carbon), a conductive carbon material (Super P), a binder composition (Example 3) and a curing agent (boron trifluoride glycerol) in a mass ratio of 90:5:40:1.
[0116] A method for preparing the above-mentioned negative electrode sheet is provided, comprising the following steps:
[0117] The negative electrode active material, the binder composition and the conductive carbon material are mixed in NMP and stirred for the first time for 120 minutes, and then a curing agent is added and stirred for the second time for 20 minutes to obtain a negative electrode slurry. The negative electrode slurry is coated on a negative electrode collector and dried at 90° C. to obtain a negative electrode sheet.
[0118] Example 4
[0119] Provided is a binder composition, the preparation method of which comprises the following steps:
[0120] Weigh 3 parts of trifluoroaniline, 4 parts of concentrated sulfuric acid, and 5 parts of concentrated nitric acid, add them into a container and stir evenly for 50 minutes. Control the temperature to 60°C and the pressure to 2.5 MPa. Pass argon gas into a closed environment to react fluorobenzene with nitric acid to generate a fluorobenzene compound with a nitro group.
[0121] After the fluorobenzene compound having a nitro group has reacted completely, the temperature is lowered to room temperature, 10 parts of bisphenol diglycidyl ester is weighed and added to the above solution, and stirred for 200 minutes to allow the epoxy group on the bisphenol diglycidyl ester to react with the nitro group of the fluorobenzene compound having a nitro group, so that the fluorobenzene compound is grafted onto the molecular chain of the bisphenol diglycidyl ester to obtain a binder composition.
[0122] Application Example 4
[0123] Provided is a negative electrode sheet, comprising a negative electrode current collector and a negative electrode layer disposed on the surface of the negative electrode current collector, wherein the negative electrode layer comprises a negative electrode active material (hard carbon), a conductive carbon material (Super P), a binder composition (Example 4) and a curing agent (boron trifluoride aniline) in a mass ratio of 84:5:35:0.7.
[0124] A method for preparing the above-mentioned negative electrode sheet is provided, comprising the following steps:
[0125] The negative electrode active material, the binder composition and the conductive carbon material are mixed in NMP and stirred for the first time for 160 minutes, and then a curing agent is added and stirred for the second time for 25 minutes to obtain a negative electrode slurry. The negative electrode slurry is coated on a negative electrode collector and dried at 90° C. to obtain a negative electrode sheet.
[0126] Application Example 5
[0127] A negative electrode sheet is provided, which is different from Application Example 1 in that the binder composition is replaced by a combination of the binder composition of Example 1 and PVDF, and the mass ratio of PVDF to NMP is 1:3.
[0128] In this application example, the total mass of the adhesive composition is the same as that of the adhesive in Application Example 1.
[0129] Application Comparative Example 1
[0130] A negative electrode sheet is provided, which is different from Application Example 1 in that, in its preparation method, the binder composition of Example 1 is replaced by a binder prepared by the following method:
[0131] Compared with Example 1, no bisphenol diglycidyl ester was added.
[0132] Application Comparative Example 2
[0133] A negative electrode sheet is provided, which is different from Application Example 1 in that, in its preparation method, the binder composition of Example 1 is replaced by a binder prepared by the following method:
[0134] Compared with Example 1, no fluorinated benzene was added.
[0135] Application Comparative Example 3
[0136] A negative electrode sheet is provided, which is different from Application Example 1 in that, in its preparation method, the binder composition of Example 1 is replaced by a binder prepared by the following method:
[0137] Compared with Example 1, bisphenol diglycidyl ester and fluorobenzene are directly mixed without undergoing a reaction.
[0138] Application Comparative Example 4
[0139] Provided is a negative electrode sheet, which differs from Application Example 1 in that, in its preparation method, the binder composition is replaced by CMC, and NMP is replaced by water.
[0140] Peel strength test: At room temperature, the negative electrode sheet was cut into a size of width × length = 25 mm × 50 mm, and the peel strength test was performed using a stretching machine, and heated to 180°C for stretching.
[0141] Assembling the battery cells:
[0142] Preparation of positive electrode sheet: Sodium nickel chromium manganate, conductive carbon black SP, positive electrode binder PVCF were mixed with an appropriate amount of NMP in a mass ratio of 95:2:3 to prepare negative electrode slurry, which was coated on copper foil respectively, dried by blast at 100°C, and cold pressed and cut into positive electrode sheets;
[0143] Battery preparation: The negative electrode sheets of application examples 1-5 and comparative application examples 1-4 are used to prepare the battery, and the positive electrode sheet, the separator, and the negative electrode sheet are wound into a core, wherein the separator completely covers the positive electrode sheet and the negative electrode sheet to obtain a core, and then the core is placed in a metal shell or wrapped with an aluminum-plastic film, and then the electrolyte is injected. Finally, a sodium ion battery is prepared through processes such as standing, formation, and capacity separation.
[0144] Low temperature electrical performance test: At -30°C, charge and discharge at a rate of 1C for 200 cycles, and calculate the capacity retention rate based on the initial discharge capacity and the discharge capacity after 200 cycles.
[0145] Room temperature cycle performance test: At room temperature (25°C), charge and discharge at a rate of 1C, taking the discharge capacity of the first cycle as the benchmark, record the number of cycles at which the capacity decays to 80% of the initial capacity.
[0146] Needle puncture safety test: After the battery cell is fully charged, use a 5-8mm steel needle to penetrate the battery cell at a speed of 25±5mm / s from a direction perpendicular to the large surface of the battery. The penetration position is close to the geometric center of the punctured surface, and the steel needle pierces the large surface of the battery cell.
[0147] The test results are shown in Table 1.
[0148] Table 1 Parameters and results of the embodiments and comparative examples
[0149]
[0150] As can be seen from Table 1, the present invention can improve the adhesion between the current collector and the active layer by introducing the above-mentioned binder composition in the preparation of the negative electrode, thereby improving the peeling force of the negative electrode and reducing the Hi-pot defect rate when preparing the pole piece; moreover, the low-temperature electrical performance and safety of the sodium ion battery can be improved. In addition, since fluorobenzene has a certain lubricity, the lubricity of the binder composition can be optimized to avoid the surface of the active layer being too rough, thereby having better processing performance.
[0151] By comparing Application Example 1 with Application Example 5 and Comparative Application Example 4, it can be seen that the specific binder composition of the present invention (including a glycidyl ester compound and a fluorobenzene compound grafted on the glycidyl ester compound) can better improve the stripping force of the negative electrode and the safety of the battery compared to conventional binders (PVDF or CMC). Moreover, the glycidyl ester epoxy resin and the fluorobenzene compound react to form a binder composition, which is more conducive to improving the stripping force of the negative electrode and the safety of the battery compared to the mixture of the glycidyl ester epoxy resin and the fluorobenzene compound. The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the scope of protection and disclosure of the present invention.
Claims
1. A binder composition, characterized in that: The binder composition comprises a glycidyl ester compound and a fluorobenzene compound grafted onto the glycidyl ester compound.
2. A method for preparing a binder composition, characterized in that: The preparation method comprises the following steps: After a nitro group is introduced into the fluorobenzene compound, the fluorobenzene compound having the nitro group is mixed with a glycidyl ester epoxy resin and reacted to obtain an adhesive composition.
3. The preparation method according to claim 2, characterized in that: The fluorobenzene compound includes at least one of fluorobenzene, difluoroaniline, trifluoroaniline and tetrafluorophenol; Preferably, the glycidyl ester epoxy resin includes at least one of bisphenol diglycidyl ester, diphenol propane and polyphenol glycidyl ester; Preferably, the mass ratio of the fluorobenzene compound having a nitro group to the glycidyl ester epoxy resin is (0.5-2):(3-6); Preferably, the mixing of the fluorobenzene compound having a nitro group and the glycidyl ester epoxy resin is accompanied by stirring; Preferably, the time for mixing the fluorobenzene compound having a nitro group with the glycidyl ester epoxy resin is 180 min to 240 min; Preferably, the process of mixing the fluorobenzene compound having a nitro group with the glycidyl ester epoxy resin is carried out at room temperature.
4. The preparation method according to claim 2 or 3, characterized in that: The method of introducing a nitro group into the fluorobenzene compound is: mixing the fluorobenzene compound, a catalyst and concentrated nitric acid, and reacting the fluorobenzene compound with the nitric acid to obtain the fluorobenzene compound having a nitro group.
5. The preparation method according to claim 4, characterized in that: The reaction of the fluorobenzene compound with nitric acid is accompanied by stirring; Preferably, the reaction time of the fluorobenzene compound and nitric acid is 30 min to 60 min; Preferably, the temperature for the reaction of the fluorobenzene compound with nitric acid is 40° C. to 70° C.; Preferably, the pressure of the reaction of the fluorobenzene compound with nitric acid is controlled within the range of 1 MPa to 3 MPa; Preferably, the catalyst comprises concentrated sulfuric acid; Preferably, the mass ratio of the fluorobenzene compound, the catalyst and the concentrated nitric acid is (0.5-2):(0.5-2):(0.5-2); Preferably, the reaction of the fluorobenzene compound with nitric acid is carried out in a closed environment, and a protective gas is passed through the closed environment; Preferably, the protective gas includes at least one of helium, nitrogen and argon.
6. A negative electrode, characterized in that The negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material and a first binder, and the first binder comprises the binder composition according to claim 1 or the binder composition obtained by the preparation method according to any one of claims 2 to 5; Preferably, the negative electrode active material is hard carbon; Preferably, the peeling force of the negative electrode active material layer is greater than 0.9N.
7. The negative electrode according to claim 6, characterized in that The negative electrode further comprises a conductive carbon material, wherein the conductive carbon material comprises at least one of conductive carbon black Super P, carbon nanotubes and graphite; Preferably, the negative electrode further comprises a curing agent, and the curing agent comprises at least one of diaminodicyclohexylmethane, triethylene glycol amine, boron trifluoride glycerol and boron trifluoride aniline; Preferably, the mass ratio of the negative electrode active material, the conductive carbon material, the first binder and the curing agent is (84-90):(5-7):(20-40):(0.5-1).
8. A method for preparing a negative electrode as claimed in claim 6 or 7, characterized in that: The preparation method comprises the following steps: (1) mixing a negative electrode active material with a first binder and first stirring to obtain a negative electrode slurry, wherein the first binder comprises the binder composition according to claim 1 or 2 or the binder composition obtained by the preparation method according to any one of claims 3 to 5; (2) coating the negative electrode slurry on a negative electrode current collector and drying to obtain a negative electrode; Preferably, the negative electrode active material is hard carbon.
9. The method for preparing a negative electrode according to claim 8, characterized in that: The negative electrode active material and the first binder are mixed and stirred for the first time, and then a curing agent is added and stirred for the second time to obtain a negative electrode slurry; Preferably, the first stirring time is 120 min to 220 min; Preferably, the second stirring time is 20 min to 45 min; Preferably, the drying temperature is 90°C to 95°C.
10. A battery, characterized in that: The battery comprises the negative electrode according to claim 6 or 7 or the negative electrode obtained by the preparation method according to claim 8 or 9; Preferably, the capacity retention rate of the battery at -30°C is greater than 90%; Preferably, the number of cycles at which the capacity of the battery decays to 80% of the initial capacity at room temperature is greater than 2000 cycles.